Altered bone development and turnover in transgenic mice over‐expressing Lipocalin‐2 in bone. Issue 11 (25th July 2013) - Costa, Delfina; Lazzarini, Edoardo; Canciani, Barbara; Giuliani, Alessandra; SpanÒ, Raffaele; Marozzi, Katia; Manescu, Adrian; Cancedda, Ranieri; Tavella, Sara
Abstract Lipocalin‐2 (LCN2) is a protein largely expressed in many tissues, associated with different biological phenomena such as cellular differentiation, inflammation and cancer acting as a survival/apoptotic signal. We found that LCN2 was expressed during osteoblast differentiation and we generated transgenic (Tg) mice over‐expressing LCN2 in bone. Tg mice were smaller and presented bone microarchitectural changes in both endochondral and intramembranous bones. In particular, Tg bones displayed a thinner layer of cortical bone and a decreased trabecular number. Osteoblast bone matrix deposition was reduced and osteoblast differentiation was slowed‐down. Differences were also observed in the growth plate of young transgenic mice where chondrocyte displayed a more immature phenotype and a lower proliferation rate. In bone marrow cell cultures from transgenic mice, the number of osteoclast progenitors was increased whereas in vivo it was increased the number of mature osteoclasts expressing tartrate‐resistant acid phosphatase (TRAP). Finally, while osteoprotegerin (OPG) levels remained unchanged, the expression of the conventional receptor activator of nuclear factor‐κB ligand (RANKL) and of the IL‐6 was enhanced in Tg mice. In conclusion, we found that LCN2 plays a role in bone development and turnover having both a negative effect on bone formation, by affecting growth plate development and interfering with osteoblast differentiation, and a positive effect on bone resorption by enhancing osteoclast compartment. J. Cell. Physiol. 228: 2210–2221, 2013. © 2013 Wiley Periodicals, Inc.